Pengaruh Lokasi, Kelengkapan Produk Dan Harga Terhadap Keputusan Pembelian Di Toko Ecky - Gideon Todianto Palobo; Dina Ramba; Rati Pundissing (CV. Aksara Global Akademia, 2024)
This research is to find out how to analyze the factors that encourage consumers to make purchases at Ecky Stores, North Toraja Regency. This type of research uses quantitative descriptive research where researchers encourage consumers to make purchases at Ecky Stores, Toraja Regency. The results of this study indicate that for the cultural factor variable, the tcount is 0.613 < ttable 1.721 and the significant level is 0.546 > 0.05, thus H1 is rejected. The results of the analysis for the completeness factor of the product are proven by the statistical results of the t-test for the dimensions of product completeness of 0.003 <0.05 and the tcount value of 1.342 > ttable 1.721 and the regression coefficient has a positive value of 0.325, so research proves that H2 product completeness factor (X2) is accepted and the results of the analysis for the price factor variable obtained a number of 0.389 > 0.05 and a tcount value of 0.880 <ttable 1.721 thus the H3 price factor (X3) is rejected.